Diffusion of Innovations Approach to the Evaluation of Learning Management System Usage in an Open Distance Learning Institution - Mkhize, Peter; Mtsweni, Emmanuel Samuel; Buthelezi, Portia (International Review of Research in Open and Distributed Learning, 2016)
Academic institutions such as the University of South Africa (Unisa) are using information and communication technology (ICT) in order to conduct their daily primary operations, which are teaching and learning. Unisa is the only distance learning university in South Africa and also in Africa. Unisa currently has the highest number of students on the continent of Africa. In an attempt to bridge the gap between facilitators and students, Unisa introduced a learning management system known as myUnisa. MyUnisa is used by facilitators and students as a tool to conduct teaching and learning, and for communication. To the best of the researcher’s knowledge, factors that influence its acceptance and usage have not been studied prior to this study. The main deciders of the success of technology are the users, as is reflected in the well-established theories and models that exist to evaluate the acceptance of technology and innovation. The objective of this study was to understand the factors that contribute to the usage of myUnisa by students. An online questionnaire was used for data collection, and a quantitative analysis was conducted. Among others, the results reveal that complexity does not have a significant impact on the students' decision to use myUnisa.